Ressignificando a produção textual na eja: uma experiência com o gênero textual carta aberta - Brito, Lidiane Moreira Silva de (2015)
The Youth and Adult Education (YAE), is a focused type of education to those who have not completed their studies at an early age. Adults returning to school in search rescue the lost time; teenagers, in turn, are in that mode, often because they failed in mainstream education for several reasons. Given this diversity of subjects, adult education becomes a mode that requires a special look, attentive to the needs of each student, which are many, and that most stand out from the point of view of teaching and learning the Portuguese language, are the difficulty with reading and writing. In this sense, this research, nature qualitative, with delineation of an action research took as its subject matter the genre open letter in order to assess to what extent the use of a didactic sequence (DOLZ, Noverraz and SCHNEUWLY, 2004) built from that gender can contribute to a better performance in the written production of 8th grade students of the 2nd segment of the Youth and Adult Education of a public school of the city of Capim-PB. To theoretically support this work, we turn to discussions of genres proposed by Bakhtin (2011), Marcuschi (2008, 2010), besides the studies on instructional sequence, developed by Dolz, Noverraz and Schneuwly (2004). The test results indicate, among other issues that the elaborate didactic sequence favored the development of language skills needed to produce writing genre open letter especially with regard to the constituent elements of that genre.